Need Assessment of Mothers’s Education Needs about Physical and Psychological Changes of the Postpartum Period in RSUP dr. Soeradji Tirtonegoro, Klaten - Sumekar, Lintang Ayu; Nisman, Wenny Artanty; Khrisnamurti, Sinta; Saryati, Rumi (Universitas Negeri Semarang, 2024)
Background: : Maternal knowledge about physical and psychological changes during the postpartum period is still low. The results of the researcher's preliminary study also prove that many mothers still experience physical and psychological problems after childbirth, because they have not received effective education. The purpose of this study is Tto explore the educational needs of mothers related to physical changes and psychological changes in the postpartum period at RSUP dr. Soeradji Tirtonegoro, Klaten .Methods: Qualitative study with descriptive phenomenological approach. Data was collected through in-depth interview. 10 participants in the polyclinic and postpartum ward were selected through purposive sampling and data analyzed using Colaizzi method. Results: This study identified 2 major themes, there is mother’s experience getting education about physical and psychological changes and postpartum mother’s education needs with normal childbirth about physical and psychological changes in postpartum period. The mother’s experience getting education about physical and psychological changes included materials, methods, media, technical, advantages, disadvantages, and educational resources. Postpartum mother’s education needs with normal childbirth about physical and psychological changes in postpartum period are educational materials, educational methods, educational media, technical education, and educational barriers. Conclusions: Postpartum mothers need educational materials about physical changes (postpartum effects, changes in the abdominal and breast area, breast milk, lochia, perineal wound care, vaginal examination) and psychological changes after childbirth. An effective method is face-to-face and the desired media is video. Education is provided during pregnancy with a duration ≦ 30 minutes. Educational barriers are lacked of participants curiosity, feeling experienced, and fear if they get unpleasant information